The Ashâarite dogma: the root of the Arab/Muslim absolutism - Mabrook, Ali (State Institute of Islamic Studies (STAIN) Salatiga, 2013)
This paper intends to initiate a serious step towards a critical investigation of thediscourse of absolutism. This paper suggests that this discourse finds its mostprofound roots in the dogmatic system of the Ashâarites. Taking for granted thatthis system is not only theological, the thesis argues that it was vulnerably usablefor ideological and political purposes. The analysis particularly focuses on tracingthe deep structure of the Ashâarite system that regulates some specific issues ina hope to touch some of its ideological functions.Tulisan ini bermaksud untuk memulai langkah serius terhadap penyelidikan kritismengenai wacana absolutisme. Makalah ini menunjukkan bahwa wacana inimenemukan akar yang paling mendalam dalam sistem dogmatis dari Asyâariyah.Mengambil begitu saja bahwa sistem ini tidak hanya teologis, tesis dari paper iniberpendapat bahwa absolutism Asyâariyah rentan dapat digunakan untuk tujuan-tujuan ideologis dan politis. Analisis ini terutama fokus pada upaya menelusuristruktur dalam sistem Asyâariyah yang mengatur beberapa isu tertentu denganharapan dapat menyentuh beberapa fungsi ideologinya.